(untitled) (Comprehensive Journal of Science, 2025)
The study aimed to measure the impact of monetary policies on Libya’s economic growth over the period 2010-2025 using annual data and economic indicators such as money supply, government expenditure, and GDP, Monetary policy is a critical tool for achieving economic stability and sustainable growth, especially in developing countries like Libya, which face economic and political fluctuations, The study employed a descriptive- analytical and applied statistical methodology based on a field survey, analyzing the relationships of interest rates, money supply, and exchange rates with economic growth rates, The findings highlighted the importance of developing monetary policy tools and central bank independence to achieve developmental galas, emphasizing the effects of interest rates and exchange rates on stability and growth, The study recommends enhancing monetary policy effectiveness to address local and regional challenges.